FEATURES OF REGULATION OF CERTAIN CRIMES AGAINST PROPERTY UNDER THE NEW CRIMINAL CODE OF THE REPUBLIC OF KAZAKHSTAN - Pirzadayev Арман Нургабылович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
The article examines the dynamics of crime against property and some criminal law in the regulation of "Theft" under the new Criminal code of the Republic of Kazakhstan on state language which will come into force from 01 January 2015.